Nanocoating Is a New Way for Biofouling Prevention - Kumar, Santosh; Ye, Fei; Dobretsov, Sergey; Dutta, Joydeep (Frontiers in Nanotechnology, 2021)
Biofouling is a major concern to the maritime industry. Biofouling increases fuel consumption, accelerates corrosion, clogs membranes and pipes, and reduces the buoyancy of marine installations, such as ships, platforms, and nets. While traditionally marine installations are protected by toxic biocidal coatings, due to recent environmental concerns and legislation, novel nanomaterial-based anti-fouling coatings are being developed. Hybrid nanocomposites of organic-inorganic materials give a possibility to combine the characteristics of both groups of material generating opportunities to prevent biofouling. The development of bio-inspired surface designs, progress in polymer science and advances in nanotechnology is significantly contributing to the development of eco-friendly marine coatings containing photocatalytic nanomaterials. The review mainly discusses photocatalysis, antifouling activity, and formulation of coatings using metal and metal oxide nanomaterials (nanoparticles, nanowires, nanorods). Additionally, applications of nanocomposite coatings for inhibition of micro- and macro-fouling in marine environments are reviewed.